EXAMINATION OF THE CHEMICAL PROPERTIES OF SEAWATER OF THE TAMBELAN ISLANDS - Suherman Suherman; Hanif Budi Prayitno (Universitas Gadjah Mada, 2012)
This research aims to investigate the quality of the Tambelan island waters as primary information to support these islands as a marine conservation area. Some chemical properties of seawater such as pH and DO (Dissolved Oxygen) were identified by portable instrumentations. Furthermore inorganic nutrients phosphate, nitrate, and silicate contents were measured according to the methods developed by Morris and Riley in 1963 and then modified by Strickland and Parsons in 1968. The results of the research show that the pH values were in the range of 8.06 to 8.30, and the DO level amounted to 5.26 to 6.31 mg/L. Further results from this research show that the content of phosphate and nitrate ranged from 0.001 to 0.004 mg/L and 0.005 to 0.018 mg/L, respectively. Meanwhile, the content of silicate was found to be 0.063 to 0.134 mg/L in the archipelagic waters of Tambelan. The values of the above parameters are in accordance with the range of the seawater quality as recommended by the Ministry of Environment of the Republic of Indonesia. Therefore, good water quality of the Tambelan islands provides great opportunities to be developed as a marine conservation area.